Comparative effectiveness research - Rogers, Mary A. M. (Oxford University Press, USA, 2013)
The last decade has seen sweeping changes in US health care policy. With more changes on the way, the emerging field of comparative effectiveness research-the science of determining how different treatments work best for different conditions-is critical for patients and clinicians who wish to make wise decisions regarding therapeutic choices. Comparative Effectiveness Research is the first textbook to offer an introduction to this topic. Written by an experienced university educator and researcher, the goal of this text is to provide readers with a gentle introduction to this diverse field. This accessible text facilitates participatory learning by including inquiries and links to web-based resources. This book will be a welcome addition to any number of courses in medicine, public health, nursing, dentistry, and allied health-or to the reference shelf of the working medical practitioner.--Publisher.